The Influence of Artificial Intelligence and the Technology Acceptance Model on Sustainable Financial Governance - Iwan Budiherwanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study investigates the influence of artificial intelligence on sustainable financial governance, both directly and indirectly through the Technology Acceptance Model. Sustainable financial governance is measured by the quality and transparency of financial reporting and by profitability, while the TAM model is represented through perceived ease of use and perceived usefulness. The research adopts an associative quantitative method, collecting primary data from 384 accounting and finance professionals across diverse sectors in Indonesia using a sampling method based on Lemeshow’s formula with a 5 percent alpha. Data analysis is conducted using least squares regression and moderated regression analysis. The study builds upon prior research using a qualitative literature review and variable feasibility assessment, aiming to provide empirical validation. The findings reveal that AI positively affects the quality and transparency of financial reports, especially when users perceive the technology as easy to use and beneficial. However, AI alone does not directly impact profitability nor moderate the relationship between ease of use and profitability. Profitability improvements are observed when users recognize the tangible benefits AI brings to their professional tasks. These results highlight the importance of user perception in realizing the potential of AI within financial governance and suggest targeted strategies to enhance technology adoption in financial sectors.